Proses Kreatif Koreografi Karya Tari â€˜Suburâ€™ - Dwi Maryani (LP2M ISBI Bandung, 2013)
ABSTRACTÂ This paper describes the creative process of choreography of fat people. It also explains that a dancer with a fat posture is not always unpleasant. A fat person is more represented, in a posi- tive way of thinking, with â€œsuburâ€ person. The questions to be discussed are: how is the character of dance movement of the fat people? And how is the choreography of the fat people in order to be looked beautiful and attractive? The creative process has been conducted through analyzing self dance movements and comprehending someoneâ€™s painting works. The result of the study shows that dances which are performed by fat people can also be looked attractive, smooth and beautiful.Â Keywords: creative process, choreographyÂ Â ABSTRAKÂ Tulisan ini menguraikan proses kreatif koreografi orang bertubuh gemuk. Tulisan ini juga menjelaskan bahwa seorang penari bertubuh gemuk tidak selalu jelek. Orang yang gemuk,Â dalamÂ pengertianÂ positif,Â lebihÂ banyakÂ diartikanÂ denganÂ orangÂ yangÂ â€˜subur â€™. Permasalahan yang diangkat ialah bagaimana karakter gerak tarian orang bertubuh ge- muk? Serta bagaimana koreografi orang bertubuh gemuk agar kelihatan indah dan me- narik? Proses kreatif dilakukan melalui penelaahan gerak-gerak dari diri sendiri serta pemahaman terhadap karya seni lukis seseorang. Hasil kajian menunjukkan bahwa ta- rian yang ditampilkan oleh orang gemuk bisa juga terlihat menarik, halus, dan indah.Â Kata kunci: proses kreatif, koreografiÂ Â